Registration of RMBHMTUP‐C4, a Random‐Mated Cotton Population Containing Alleles from Four Gossypium Species. Issue 3 (1st September 2019) - Jenkins, Johnie N.; McCarty, Jack C.; Hayes, Russell W.; Stelly, David M.; Saha, Sukumar
Abstract : The genetic base for upland cotton ( Gossypium hirsutum L.) breeding needs more diversity. Use of Gossypium wild species is of interest to breeders, but interspecific crosses between G. hirsutum and wild tetraploid species or the cultivated tetraploid species G. barbadense L. have not been widely used due to the extreme difficulty of extracting elite lines in later generations. Following a nonconventional breeding approach, we used 32 chromosome substitution lines to capture allelic diversity from three donor tetraploid Gossypium species and combined that with the intraspecific allelic diversity among five upland cultivars. By random‐mating the 32 F1 hybrids and subsequent generations for five cycles, the intra‐ and interspecific diversity from four Gossypium AD‐genome species was combined in a new random‐mated population dubbed R andom M ated B arbadense, H irsutum, M ustelinum, T omentosum, U pland P opulation (RMBHMTUP‐C4; Reg. no. GP‐1061, PI 690471). This unique population should facilitate efforts to diversify the genetic base for upland cotton breeding. Despite its allelic diversity, this population has average phenotypic and fiber characteristics much like an upland cultivar. During development, we did not observe breeding problems normally observed in conventional interspecific crosses. This should add to the usefulness of this population for introgression of alleles from these tetraploid species. We harvested about 2209 bolls each cycle of random mating (11, 045 bolls). Assuming 25 seed per boll, this equates to 276, 125 hand‐crossed seed, each from union of two genetically unique gametes.